The Role of the Mass Media on the Issues of Religious Blasts in the Sharia Maqasid Concept - Benny Munardi (INJECT (Interdisciplinary Journal of Communication), 2021)
This study aims to describe the role of mass media on the issue of blasphemy in the concept of maqashid sharia. The theory used in this research is agenda setting in which the power of the media has a very strong influence on humans, thus forming certain emotions with the issues raised by the mass media. The type of research and the approach used is descriptive-qualitative like library research, which takes data from the case of blasphemy Joseph Paul Zhang through his YouTube account and the Waspada daily newspaper. Data collection techniques were carried out by literature study and documentation. Data analysis is inductive with data reduction stages, then data presentation and verification. The results of the study show that the role of the mass media in overcoming cases of blasphemy news cannot be filtered out and can easily be accessed by the public in cybercrime, the media is easily polished by the owner of the interest, so that the issues circulating are not balanced, in the case of blasphemy the media can only be a bridge and return to the public to respond to the news circulating.